Estimating the degree of novelty of a new product: innovative approach - Vasyutinska, Julia; Kuzminska, Natalia (My University, 2019)
The article summarizes the arguments and counterarguments within the scientific discussion on determining the structure and degree of novelty of the goods according to the classification in terms of the functional orientation of the novelty of the goods. The main purpose of the study is to develop their own methodology for assessing the degree of novelty of a new product as a quantitative characteristic based on comparison with the analog product. In order to build a methodology, it is important to justify the scale of the novelty of a product: a regional, national or global market. The determination of the necessary scale of novelty depends on the choice of the main analog product and the choice of the consumer group. The systematization of literary sources and approaches to solving the problem of determining the level of novelty of the goods showed that there is no universal method of assessing the degree of its novelty. The urgency of solving this scientific problem lies in the assessment of the degree of novelty of the goods, because in reality the market is full of pseudo-new goods. The concept of novelty is relatively relative and has no clearly defined requirements. The research of quantitative evaluation of novelty of goods in the article is carried out in the following logical sequence: the essence and structure of novelty is determined, the level of novelty for each species is estimated and the overall integral index is output. The mathematical methods of the actions with the matrices and the methods of analyzing the hierarchies of pairwise comparisons, proposed by Thomas L. Saati, became a methodological tool of the conducted research. Comparison of indicators against different criteria is made on a nine-point scale. The integral measure of novelty level of a new product is calculated as the geometric mean of production, market and consumer novelty indicators. The novelty level of a new product is determined on a scale from 0 to 1, which allows to determine the novelty for each type of novelty and for the general level of novelty of the product. The results of the study may be useful for evaluating the enterprises of their new goods and as a component of evaluating the innovative activity of enterprises.
Keywords: новизна; новий товар; кафедра вищої математики імені проф. Можара В. І.; novelty